Electromecánica automotriz y su incidencia en la calidad de vida de los estudiantes del tercer año de bachillerato de la Unidad Educativa Técnico Alborada del cantón Milagro, provincia del Guayas - Cortez Campoverde, Urbano (2017)
Due to the constant changes to which we are subjected in the new century, we are obliged to raise new ideas, one of those has to do with Education that is constantly changing and trying to update traditional teaching methods, where the demands project to train students, graduates and why not say competent professionals with an autonomous, scientific and technological formation to one way or another satisfy the society, contributing with a qualified workforce that develops in a creative, participative and collaborative way between each other, and innovating practical processes for the solution of problems that arise in the development of the skills and values acquired in the learning process of the subject of Automotive Electromechanics. The following research project is intended to provide an accurate way to improve the theoretical and practical learning of automotive electromechanics, through the Project of Improvement in Theoretical-Practical Learning and Repowering of the Career Practice Workshop. Electromechanics Automotive. The methodology used is related to the updating of theory and information technologies that facilitate the interrelation and consolidation of theoretical knowledge with practical knowledge, facilitating students to focus on a modern educational model that allows them to obtain knowledge in accordance with the demands of the labor market in the automotive area that manages to improve the quality of life of students based on what they learned in their collegiate stage